Research integrity guidelines in the academic environment: The context of Brazilian institutions with retracted publications in health and life sciences - Rafaelly Stavale; Rafaelly Stavale; Vanja Pupovac; Graziani Izidoro Ferreira; Dirce Bellezi Guilhem (Frontiers in Research Metrics and Analytics, 2022)
Although research misconduct is responsible for most retractions in health and life sciences from authors affiliated with Brazilian institutions, there are few studies evaluating retraction notices and research misconduct in the country. Understanding the form of research misconduct may share light on the weaknesses and strengths of individual, organizational, and structural factors toward the implementation of a research integrity culture. This review on policies and practices aims to access the available information from research integrity offices and the guidelines from Brazilian funding institutions and universities who were involved in retractions in health and life science publications based on a previously published systematic review. Additionally, we summarize the available guidelines and policies for research integrity in the country. Additionally, we searched publicly available guidelines and offices for research integrity. In total, 15 institutions were analyzed: five funding agencies and 10 universities. Approximately 40% of the funding agencies promoted local research, and 60% promoted national research. Considering national funding agencies, 66% had the commission on research integrity. Approximately 30% of the universities do not have the official office for research integrity or any publicly available guidelines. Most institutions involved in retractions due to some form of research misconduct. Brazilian institutions involved in publication retractions lack instruments to prevent, supervise, and sanction research misconduct. Institutions of the country have insufficiently developed a system to promote and sustain research integrity practices. Nevertheless, there is a positive movement of researchers who are engaged in the investigation of research integrity, policy creation and training. This study emphasizes increased influence of Brazilian scientific collaboration and production globally as well as the impact of retractions in medical sciences. In contrast, it addresses the need for clear research integrity policies to foster high-quality and trustworthy research.